2008
DOI: 10.1111/j.1939-1676.2008.0168.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetyl‐β‐d‐Glucosaminidase Index as an Early Biomarker for Chronic Kidney Disease in Cats with Hyperthyroidism

Abstract: Background: Hyperthyroid cats are at risk of developing azotemic chronic kidney disease (CKD) and diagnostic tools currently used to screen for CKD in hyperthyroid cats are either unreliable or impractical.Hypothesis: Urine N-acetyl-b-D-glucosaminidase index (NAG i ) is a good biomarker for azotemic CKD in hyperthyroid cats.Animals: Twenty-four newly diagnosed nonazotemic hyperthyroid cats and 10 healthy cats. Methods: All cats were evaluated for hyperthyroidism at baseline. Hyperthyroid cats were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
3

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 38 publications
(66 reference statements)
5
27
0
3
Order By: Relevance
“…18,19 It also has been evaluated as a biomarker for the development of azotemia in hyperthyroid cats treated with methimazole. 20 In that study, NAG indexed to urinary creatinine was unable to differentiate cats at risk of developing azotemia. Recent data from our group indicated that the correlation between NAG index and plasma creatinine concentration is poor, but that NAG index may correlate with the magnitude of proteinuria.…”
Section: Abbreviationsmentioning
confidence: 87%
“…18,19 It also has been evaluated as a biomarker for the development of azotemia in hyperthyroid cats treated with methimazole. 20 In that study, NAG indexed to urinary creatinine was unable to differentiate cats at risk of developing azotemia. Recent data from our group indicated that the correlation between NAG index and plasma creatinine concentration is poor, but that NAG index may correlate with the magnitude of proteinuria.…”
Section: Abbreviationsmentioning
confidence: 87%
“…Although proteinuria usually resolves after treatment of hyperthyroidism, its presence prior to treatment is correlated with reduced survival but not development of azotemia (Williams et al, 2010b). Although these markers are present in the urine of hyperthyroid cats, they have not proved useful in predicting which cats are likely to become azotemic after treatment (Lapointe et al, 2008;van Hoek et al, 2009b). In one study urine culture was positive in 11 of 90 (12%) of hyperthyroid cats, and 17 of 77 (22%) cats with CKD.…”
Section: Urinalysismentioning
confidence: 99%
“…Ademais, gatos com insuficiência renal crônica demonstraram elevação dessa enzima antes da elevação das concentrações séricas de ureia e creatinina (SATO et al, 2002). Essa enzima também pode ser uma ferramenta interessante na monitoração da lesão renal progressiva durante a terapia de gatos com hipertireoidismo (LAPOINTE et al, 2008). Não existem kits laboratoriais no Brasil disponíveis para a realização deste exame.…”
Section: Enzimas Urináriasunclassified